III Rajd Politechniki Gdańskiej Pierwiosnki 67. (Gdynia : [s.n.], 1967)
Afisz inf. o rajdzie.
Keywords: Politechnika Gdańska -- 1945-1990 -- druki ulotne; Turystyka -- Polska -- 1945-1970.; Gdańsk (Polska) -- 1945-1970 -- druki ulotne